PENGEMBANGAN KARTU BERSERI PINTAR, TAAT, DAN RAJIN (PINTARA) UNTUK MENUMBUHKAN DISIPLIN POSITIF PADA ANAK USIA DINI - Diny Veronica; Lilis Suryani; Ajat (Program Studi pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2025)
This study aims to develop the Pintar, Taat, and Rajin (Pintara) Serial Story Cards to foster positive discipline in early childhood, particularly in queuing, sharing, and tidying up toys. The background of this research lies in the dominance of instructive methods in early childhood education, which are less engaging and ineffective in building children’s intrinsic discipline. This study employs a Research and Development (R&D) method using the ADDIE model, limited to the development stage. Trials were conducted individually, in small groups, and in large groups with children aged 5–6 years in Mustika Jaya District. Data were collected through observations, interviews, expert validation questionnaires, and children’s response assessments, then analyzed qualitatively and quantitatively. The results indicated that the Pintara cards met the principles of early childhood learning, were deemed highly feasible by experts and practitioners with an overall category of “very good”, obtaining an average percentage score of 90% from the material expert, 95% from the media expert, and 97.5% from early childhood education practitioners, and received positive responses from children with most respondents (43.33% of the total 30 participants) categorized as “very good”. Children found it easier to understand moral messages, were motivated to practice discipline, and showed improvements in queuing, sharing, and tidying behaviors. Thus, the Pintara Serial Story Cards are feasible to be used as an innovative medium to foster positive discipline in early childhood.